2020
DOI: 10.1620/tjem.252.15
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Interval between Onset and Admission to Convalescent Rehabilitation Wards Is Associated with Improved Outcomes in Ischemic Stroke Patients

Abstract: As Japan's population ages, there is a growing interest in regional health care coordination. Our study aimed to evaluate whether the interval between onset and admission to convalescent rehabilitation wards (onset-admission) was associated with outcomes in ischemic stroke patients. We conducted a retrospective cohort study in a single rehabilitation hospital. Ischemic stroke patients consecutively admitted to the wards were eligible to enroll. Outcomes included Functional Independence Measure (FIM)motor gain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
2
7
2
Order By: Relevance
“…Multivariate logistic regression analysis revealed that age, duration from stroke onset to admission, living situation, and FIM motor score at admission were also associated with home discharge in subacute stroke patients. Previous studies have reported the association between discharge and age [8], duration from stroke onset to admission [14], social factors [7-9, 11, 15, 17], and FIM score [6, 8, 10, 16]; these ndings are consistent with our ndings. Therefore, it is essential to prepare for home discharge by assessing cognitive function and considering age, social factors, and ADL ability at admission in subacute stroke patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariate logistic regression analysis revealed that age, duration from stroke onset to admission, living situation, and FIM motor score at admission were also associated with home discharge in subacute stroke patients. Previous studies have reported the association between discharge and age [8], duration from stroke onset to admission [14], social factors [7-9, 11, 15, 17], and FIM score [6, 8, 10, 16]; these ndings are consistent with our ndings. Therefore, it is essential to prepare for home discharge by assessing cognitive function and considering age, social factors, and ADL ability at admission in subacute stroke patients.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported factors related to home discharge in patients with subacute stroke [6][7][8][9][10][11][12][13][14][15][16][17][18]. In particular, many studies have consistently suggested that functional disability is related to home discharge.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, covariates selected to adjust bias included age, sex (male), LOS, CCI, FIM-motor, and FIM-cognitive on admission, FILS on admission, energy intake on admission, and total rehabilitation therapy (units/day), all of which were previously reported to be clinically relevant predictors of rehabilitation outcomes. [32][33][34][35][36] To reduce bias, adjustment for common confounders was performed via a series of multivariate analyses outcomes. Multicollinearity was assessed via variance in ation factor (VIF), with values ranging from 1 to 10 indicating the absence of multicollinearity.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline patient demographic characteristics were recorded upon admission, including age, sex, body mass index, stroke type, stroke history, days from stroke onset to admission [ 17 ]; nutritional status, assessed using the Mini Nutritional Assessment-Short Form (MNA-SF) [ 18 ]; swallowing status, assessed using the Food Intake Level Scale (FILS) and presence of dysphagia requiring supplemental feeding defined by the FILS scores <7 [ 19 ]; comorbidities, assessed using the Charlson Comorbidity Index (CCI) [ 20 ]; and premorbid ADL, assessed using the modified Rankin Scale (mRS) [ 21 ]. Information was collected on the presence of paralysis and localization and stage of paralysis according to the Brunnstrom recovery stages (BRS) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%